2008
DOI: 10.1074/jbc.m805848200
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of the Seesaw Mechanism of the Relay Region That Moves the Myosin Lever Arm

Abstract: A seesaw-like movement of the relay region upon the recovery step of myosin was recently simulated in silico. In this model the relay helix tilts around its pivoting point formed by a phenylalanine cluster (Phe 481 , Phe 482 , and Phe 652 ), which moves the lever arm of myosin. To study the effect of the elimination of the proposed pivoting point, these phenylalanines were mutated to alanines in two Dictyostelium myosin II motor domain constructs (M F481A, F482A and M F652A ). The relay movement was followed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…The lever swing in ATP (recovery step) and ADP–P i states (futile lever swing), associated with switch 2 conformational changes, has been proposed to involve a seesaw-like movement of the long relay helix within the motor domain [12]. In the middle of the relay helix, a phenylalanine cluster forms a fulcrum around which the tilt might occur [12,13]. This cluster structurally connects the relay/converter and transducer regions.…”
Section: Futile Lever Swing Is Kinetically Blockedmentioning
confidence: 99%
“…The lever swing in ATP (recovery step) and ADP–P i states (futile lever swing), associated with switch 2 conformational changes, has been proposed to involve a seesaw-like movement of the long relay helix within the motor domain [12]. In the middle of the relay helix, a phenylalanine cluster forms a fulcrum around which the tilt might occur [12,13]. This cluster structurally connects the relay/converter and transducer regions.…”
Section: Futile Lever Swing Is Kinetically Blockedmentioning
confidence: 99%
“…We showed that in Dictyostelium myosin II, actin binding in the presence of ATP straightens the relay helix before dissociation of hydrolyzed phosphate (5). If the straight structural state of the relay helix is tightly coupled to the postpower stroke orientation of the LCD as proposed (14,15), then actin should induce LCD rotation before phosphate release. This hypothesis disagrees with several existing proposals (2, 4) but agrees with recent studies performed in isolated muscle fibers (6).…”
Section: Significancementioning
confidence: 99%
“…The structure of this helix is allosterically coupled to interactions between switch-2 and bound ATP, ADP, and hydrolyzed phosphate (14,15). Movement of the relay helix is hypothesized to be tightly coupled to LCD rotation (14)(15)(16).…”
Section: Significancementioning
confidence: 99%
“…S1 shows a simple illustration of the method. Examples of applications include a bacterial pore (21) and myosin (5), for which the transition mechanism found by CPR was subsequently verified by experiment (22).…”
mentioning
confidence: 99%